MUHAMMAD IBN ‘ABD AL-WAHHÂB DAN GERAKAN WAHABI - Mangasing, Mansur (Hunafa: Jurnal Studia Islamika, 2008)
In the Islamic world, in the middle age, the ideas on reformation and the efforts of purification of akîdah had  emerged. This was a reaction against the extant political condition and tauhid comprehension of Muslims. In  Arab, a chief figure, Muhammad ibn ‘Abd al-Wahhâb who possessed a great concern towards the matter of akîdah purification of Muslims and Islamic reformation, emerged. The efforts of al-Wahhâb finally developed into a movement called the Wahabiyyah Movement. The main target of this movement was to purify Muslims’ akîdah that had been mixed with heretics. Kata Kunci:    Muhammad ibn ‘Abd al-Wahhâb, Gerakan Wahabi, pemurnian Islam, pembaruan Islam